Emergence of Weyl fermions by ferrimagnetism in a noncentrosymmetric magnetic Weyl semimetal - Cong Li; Jianfeng Zhang; Yang Wang; Hongxiong Liu; Qinda Guo; Emile Rienks; Wanyu Chen; Francois Bertran; Huancheng Yang; Dibya Phuyal; Hanna Fedderwitz; Balasubramanian Thiagarajan; et al. (Nature Communications, 2023)
Abstract Condensed matter physics has often provided a platform for investigating the interplay between particles and fields in cases that have not been observed in high-energy physics. Here, using angle-resolved photoemission spectroscopy, we provide an example of this by visualizing the electronic structure of a noncentrosymmetric magnetic Weyl semimetal candidate NdAlSi in both the paramagnetic and ferrimagnetic states. We observe surface Fermi arcs and bulk Weyl fermion dispersion as well as the emergence of new Weyl fermions in the ferrimagnetic state. Our results establish NdAlSi as a magnetic Weyl semimetal and provide an experimental observation of ferrimagnetic regulation of Weyl fermions in condensed matter.